Diversity of Makrozoobenthos as Bioindicators of the Quality of the Waters in Sibolga - ryan, ryan; Schucyan, M. (International Journal of Science, Technology & Management, 2020)
ABSTRACT The waters of sibolga is the waters are very widespread in , this area is densely populated, so there are many community activities that take place such as Transportation, Fisheries, Bathing, sand Mining and other.The purpose of this study is to determine the role of macrozoobenthos as a bioindicator of water quality in the waters of Sibolga Tapanuli Tengah, as well as determine the quality of water in the flow of the waters Sibolga physical properties, chemical has. The research was conducted from November 2019 to February 2019, the samples taken from the three research stations. From the results obtained Macrozoobenthos in the identification in this study consisted of 3 Phyla of invertebrates namely : Annelids, which consists of 2 classes, Arthropods consisting of 1 class and Molusca, which consists of 1 class. Based on the data of macrozoobenthos obtained at each research station, then the obtained value of population density, relative density and frequency of presence of that at station I the value of its highest density is Tubifex sp. with the value of the density of the population of 18,519 individual/m2, the density is relatively 25,862% and the frequency of the presence of 55,555%. off at 3. at station 2 the highest density is Tubifex sp. with the value of the density of the population of 18,519 individuals/m2, relative density 25,862% and a frequency of 55,555%. also note that the total score obtained by the method storet, namely -30, this shows that if connected with the raw water quality of class I is then classified in the waters of class III, which means that light polluted. The high total score method storet on the entire research station due to the presence of a variety of activities at each of the stations, settlements, sand mining and other activities. Where these activities produce waste, which in the end increases the content of Phosfat, COD, TSS and BOD5, thus causing the waters of the Waters of Sibolga is light polluted. Kata kunci : makroozoobentos, Sibolga and bioindikator